Riverine Field Oil Spill Experiment - Al-Asadi, Manal Kamil Khalaf (University of Thi-Qar Journal of Science, 2013)
This study concern the case of oil spill in the river Shatt al-Arab- site (Muftia) to understand theenvironmental conditions affecting during the case of oil spill accident.It was found that there is privacy in such environment, during exposure to spilled oil, considering that such areas are characterized by high water temperature, long day light, And a special bacterial activity.To understand such circumstances affecting the spilled oil. A gas liquid chromatography technique was used by selection the n-alkanes in this crude oil, the analysis of their n-alkanes reduced in concentration from 370- 93 ug/g in crude oil before spill to 12.00 ug/g after 164 days of spill oil by 96.77% removal.